UNIT 27.8 Post‐Translational Modification Profiling—a High‐Content Assay for Identifying Protein Modifications in Mammalian Cellular Systems. (1st August 2014) - Merbl, Yifat; Kirschner, Marc W.
Abstract: Protein microarrays are extremely useful for detecting substrates of phosphorylation, substrates of ubiquitylation, or other post‐translational modifications. The ability to screen binding interactions as well as post‐translational modifications of thousands of proteins at once has improved our ability to identify their targets. Utilizing such systems in combination with functional mammalian cell extracts that preserve enzymatic activity offers advantages in identifying semi‐quantitative changes of these interactions in the context of specific cellular conditions. This unit provides a detailed procedure for setting up an extract‐based activity assay for high content detection of protein post‐translation modifications. It also provides basic guidelines for data analysis. Curr. Protoc. Protein Sci . 77:27.8.1‐27.8.13 © 2014 by John Wiley & Sons, Inc.